2014
DOI: 10.1371/journal.ppat.1003903
|View full text |Cite
|
Sign up to set email alerts
|

Origin, Migration Routes and Worldwide Population Genetic Structure of the Wheat Yellow Rust Pathogen Puccinia striiformis f.sp. tritici

Abstract: Analyses of large-scale population structure of pathogens enable the identification of migration patterns, diversity reservoirs or longevity of populations, the understanding of current evolutionary trajectories and the anticipation of future ones. This is particularly important for long-distance migrating fungal pathogens such as Puccinia striiformis f.sp. tritici (PST), capable of rapid spread to new regions and crop varieties. Although a range of recent PST invasions at continental scales are well documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
345
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 280 publications
(375 citation statements)
references
References 62 publications
27
345
3
Order By: Relevance
“…In Australia, YR is the most damaging rust disease, causing average annual economic losses of AUD$127 million (71). Schematic overview of the recent emergence and spread of important new races of stripe rust fungus (2,37,38,39). The spread of PstS1 to the United States and Australia represents the introduction of a single lineage.…”
Section: Yellow Rustmentioning
confidence: 99%
“…In Australia, YR is the most damaging rust disease, causing average annual economic losses of AUD$127 million (71). Schematic overview of the recent emergence and spread of important new races of stripe rust fungus (2,37,38,39). The spread of PstS1 to the United States and Australia represents the introduction of a single lineage.…”
Section: Yellow Rustmentioning
confidence: 99%
“…For example, microsatellite genotyping revealed that six major geographical clusters comprise the global population of wheat yellow rust fungus (Puccinia striiformis f. sp. tritici ) and the Himalayas to be the center of origin for this pathogen, with human activities as the most likely cause of spread (2).…”
Section: Patterns and Processes Of Changing Distributionsmentioning
confidence: 99%
“…The tested pathogen Pst has a high genotypic diversity and is capable of reproducing among geographically distant populations [Ali et al, 2014]. It is particularly relevant for risk assessments and predictions of the worldwide spread of plant diseases.…”
Section: Discussionmentioning
confidence: 99%